2020
DOI: 10.1177/0735633120953598
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Smartphone-Controlled Paper Airplane Into Gamified Science Inquiry for Junior High School Students

Abstract: Integrating science learning with game experience and physical manipulatives not only overcomes the rigidity of traditional teaching, but also makes the learning experience pleasant for students and improves their science inquiry ability. Today, with the popularization of mobile devices and technology, both the value and feasibility of gamified science learning have increased significantly. However, several studies showed that students might get lost or feel bored during science inquiry. To let students enjoy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Positively speaking, science popularization itself is a form or approach of education, so the new changes of science popularization contribute to the changes of higher education; in other words, science popularization development facilitates the growth of higher education with more pertinence [ 6 , 27 , 28 ]. Secondly, science popularization activities enhance university students’ passion or motivation for and participation in study, which lead to better performances and competitiveness in higher education [ 11 , 29 ]. Cases have proved that science popularization is helpful to accelerate the learning outcomes of students in colleges, such as writing skills, literature understanding, physics knowledge acquisition, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Positively speaking, science popularization itself is a form or approach of education, so the new changes of science popularization contribute to the changes of higher education; in other words, science popularization development facilitates the growth of higher education with more pertinence [ 6 , 27 , 28 ]. Secondly, science popularization activities enhance university students’ passion or motivation for and participation in study, which lead to better performances and competitiveness in higher education [ 11 , 29 ]. Cases have proved that science popularization is helpful to accelerate the learning outcomes of students in colleges, such as writing skills, literature understanding, physics knowledge acquisition, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, lacking sufficient focus on science popularization is likely to decrease higher education competitiveness; science popularization activities are good opportunities for students to learn new skills or knowledge, and lacking enough related activities reduces studying chances and competitiveness of college students, which in turn reduces higher education competitiveness [ 36 ]. It is also found that some science popularization activities may make students feel boring or lost [ 29 ]. Thirdly, some debates or problems may occur in science popularization programs (such as ethical issues, legal issues, social norm issues, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, there is a lot of situationality in gamification. Therefore, according to M. Cheng, S. Su, and C. Kinshuk, in order to reveal the content of this concept, as well as to define the game, it is important to understand the goal of the developers, as well as to see the perception of the participants (Cheng et al, 2021).…”
Section: Analysis Of Foreign Studiesmentioning
confidence: 99%
“…The system of traditional classroom education will have to change to meet the needs of a new, more comprehensive approach to education and the development of the student's personality. As a result, it is the teacher in the digital school who will be responsible for integrating game mechanics into the classroom (Cheng et al, 2021). Only such methodological work will allow gamification to fit seamlessly into a single information educational space.…”
Section: Introduction 1relevance Of the Problemmentioning
confidence: 99%
“…Flow is defined as a child's psychological state of full engagement in an activity (Csikszentmihalyi, 1977). Researchers have found that flow is positively related to children's learning performance and motivation for continuous learning (Cheng et al, 2021). Besides, flow associates with children's divergent thinking which benefits their creative problem-solving abilities (Chu et al, 2015).…”
Section: Alternate Reality Gamesmentioning
confidence: 99%